BRS Saturno triticale cultivar - Nascimento Junior,Alfredo do (2011)
The triticale cultivar BRS Saturno was developed by Embrapa (Brazilian Agricultural Research Corporation) in partnership with the Fundação Pró-Sementes de Apoio à Pesquisa. It is the result of a cross between the genotypes PFT 512 and CEP 28 Guará, adapted to the environmental conditions of cultivation in southern Brazil.